ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DITINJAU DARI GAYA KOGNITIF PADA MATERI SISTEM PERSAMAAN LIENAR DUA VARIABEL - Feri, Julius (UNIVERSITAS TANJUNGPURA, 2024)
This study uses descriptive and qualitative research techniques. Data are collected and described in the form of words in descriptive research. This research was conducted at SMP Awaluddin. The data of this study were collected through certain methods, namely, tests, questionnaires, interviews used to analyze difficulties regarding mathematical creative thinking skills in the material of two-variable linear equations, then processed into clear and easy-to-understand information. The subjects in this study consisted of 6 students of grade VIII with 2 students who had high, medium, and low levels of ability in each with a field dependent cognitive style consisting of 1 student and a field independent cognitive style consisting of 1 student. Data collection techniques used in this study are measurement techniques, direct communication techniques and indirect communication techniques with data collection tools in the form of test questions, questionnaires, and interview guidelines. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results obtained by students who have high creative thinking abilities fulfill the three indicators of aspects of thinking ability, namely fluency, flexibility and novelty, (2) Students with moderate creative thinking abilities show that they only fulfill the fluency aspect, (3) Students with low mathematical creative thinking abilities do not fulfill the three aspects of creative thinking abilities, namely fluency, flexibility and novelty.Keyword: analysis, creative thinking skills, cognitive style, SPLDV